(untitled) (Journal of Rangpur Medical College, 2024)
Background: Eclampsia is a severe and life-threatening complication of pregnancy, characterized by the onset of seizures in a woman with preeclampsia. This hypertensive disorder of pregnancy is associated with a range of maternal complications, presenting a significant challenge in obstetric care. Maternal complications of this nature can significantly affect both maternal and perinatal health, potentially leading to higher rates of mortality and morbidity. Objective: This study was aimed to evaluate the morbidity and mortality of eclampsia in Brahmanbaria Medical College and Hospital. Methods: This cross-sectional observational study was conducted at Brahmanbaria Medical College and Hospital, Brahmanbaria, Bangladesh, from January 2021 to December 2021. The study included 56 pregnant women with eclampsia purposively. Demographic and clinical information was recorded, and data analysis and dissemination were carried out using MS Office tools. Results: Regarding perinatal outcomes, 80% of cases resulted in live births, with a 57% survival rate. Among live births, 4% experienced post-birth mortality, and 11% faced early neonatal death. Among live births (n=45), a significant 69% experienced intrauterine growth restriction (IUGR). Maternal complications included abruptio placenta in 32% of cases, HELLP syndrome in 5%, and maternal death occurred in 5% of cases. Conclusions: Eclampsia assessment shows complex perinatal and maternal outcomes. Live births are common, but survival is challenging. High post-birth and neonatal mortality highlight newborn vulnerability. Intrauterine growth restriction (IUGR) worsens newborn health concerns. Maternal issues like abruptio-placenta, HELLP syndrome, and maternal death further complicate matters. J Rang Med Col. March 2024; Vol. 9, No. 1: 39-43